Gastroesophageal Reflux Disease: Diagnosis and Patient Selection - Singhal, Vikas (Indian J Surg, 2014)
Gastroesophageal reflux disease (GERD) has a high prevalence worldwide. Recent reports have noted a high prevalence even in Asian countries. GERD significantly affects the quality of life and can present with a wide variety of symptoms. Not all reflux is acid, and non-acid reflux disease can be more difficult to diagnose and can lead to a variety of extra-esophageal symptoms. Although proton pump inhibitors (PPIs) are effective in the majority of patients, but they are not without side effects, and their effect often diminishes with time. For patients who do not desire to be on long-term PPIs or have incomplete symptom resolution with medication, various endoscopic and minimally invasive treatment modalities are now available. The etiology of GERD can be multifactorial including dysfunctional LES, presence of a hiatal hernia, and transient lower esophageal sphincter relaxations (TLESRs). We hence believe that the treatment should be individualized to the cause of the reflux. In the following review, we describe the etiology of reflux disease and attempt to lay a framework for the diagnosis and selection of patients for the various interventions available for treatment, along with their evidence base.